Topical Fisionerv® is effective in treatment of peripheral neuropathic pain - Tarullo, Angelo; Tarullo, Antonella; Lacatena, Emanuela; Santacroce, Luigi; Inchingolo, Angelo Michele; Malcangi, Giuseppina; Scacco, Salvatore; Fanelli, Margherita; Cagiano, Raffaele; Inchingolo, Francesco; Caprio, Monica; Dipalma, Gianna; et al. (Acta Biomedica Atenei Parmensis, 2019)
Background: Management of neuropathic pain (Neu P) is complex and difficult. Although there are several therapeutic options, treatment with Neu P is often inadequate, which led to undertreated patients. Thus, it would be desirable, for Neu P treatment, further multimechanistics approaches. Objective: The aim of the present study was to evaluate, in Neu P management, the effectiveness of “FISIONERV, a gel for topical use. Setting: This study was conducted in the “Rehabilitation Unit of N. Melli’s Hospital, Brindisi, Italy”. Patients and intervention: In this study a double- blind randomized controlled clinical trial was conducted over 8-week treatment on 58 outpatients affected by Neu P caused by lumbar sciatica or lumbar disk herniation and/or lumbar canal stenosis (31 subjects), or with carpal tunnel syndrome (27 subjects), randomly assigned to the following two groups: Group A; n=29, received (fisionerv® gel, 3 times/day) added to physiotherapy (forty minutes-daily session). Group B; n=29 received a vehicle gel (placebo, 3 times/day) added to physiotherapy (forty minutes-daily session). Measurements: Pain was assessed by a visual analogue scale (VAS). Neuropathic symptoms frequency (pain, burning, paraesthesiae and numbness) were scored at baseline and at the end of the treatment. Treatment compliance and safety were also evaluated. Results: Both groups experienced a significant reduction in VAS and neuropathic symptoms after 8-treatment weeks. However, a significant (p<0.05) improvement was observed in group A (VAS mean 5.3 (1.10) with respect to group B (VAS mean=6.17 (0.80), already after 4 weeks of treatment. A further VAS reduction was recorded at 8 treatment weeks, with significant difference between the treatments (group A: VAS mean=1.89 (0.77); group B: VAS mean=3.79 (1.20) (p<0.001). In addition, more patients of the group A, than in group B, reported an improvement of their neurophatc pain (p<0.01). No adverse drug reaction was observed. Conclusion: Use of fisionerv®, in combination with physiotherapy, resulted a useful approach to NP treatment. Clinical rehabilitation impact: These preliminary observations suggest that some interesting goals (better pain control and physical wellbeing) could be achieved by a multimodal therapy in NP patients.